KETIKA INFLASI DAN KETIDAKPASTIAN MENEKAN: REFLEKSI DOOM SPENDING DAN PENTINGNYA LITERASI EKONOMI - Amelia, Shella Rizqi; Anah, Lik; Ulya, Widadatul (UNPERBA, 2025)
The phenomenon of doom spending, or impulsive consumption behavior as an emotional escape, has become increasingly prevalent amid global economic uncertainty. Economic crises, high inflation, and job insecurity are key drivers of irrational consumer behavior. This study aims to systematically review the literature examining the relationship between macroeconomic pressures, doom spending behavior, and the role of economic literacy as a mitigation tool. Using a systematic literature review approach, this research analyzes scholarly articles published between 2018 and 2025 from reputable sources. The findings indicate that macroeconomic pressure significantly contributes to doom spending behavior, and economic literacy plays an essential role in shaping rational consumer decision-making. However, economic literacy alone is insufficient without self-regulation and digital awareness of consumerist influences. This study highlights the urgency of enhancing economic literacy programs that are adaptive to digital challenges and macroeconomic dynamics. Keywords: doom spending, economic literacy, macroeconomic pressure, consumer behavior, literature review